COMT genotype and resting brain perfusion in children - Thomason, Moriah E.; Waugh, Christian E.; Glover, Gary H.; Gotlib, Ian H. (NeuroImage (Orlando, Fla.), 2009)
Levels of extra-synaptic dopamine in the brain vary as a function of polymorphisms at the val158met locus of the catechol-O-methyltransferase ( COMT) gene. In vivo studies of this polymorphism in the human brain have typically measured patterns of neural activation during dopamine-mediated tasks in adults. This study is the first to investigate the effects of COMT on brain physiology during rest and in children. We used flow-sensitive arterial spin-labeling (ASL) magnetic resonance imaging to examine brain blood flow (CBF) in 42 children. Compared with val-allele carriers, met-allele homozygotes exhibited greater CBF in mesolimbic, mesocortical, and nigrostriatal dopamine (DA) pathways. Higher CBF in DA-rich brain structures reflects COMT-related baseline differences that (1) underlie the selective behavioral advantages associated with each genotype; (2) affect interpretations of previously reported genotype differences in BOLD signal changes; and (3) serve as a foundation for future studies on the effects of COMT on brain development.